2013
DOI: 10.1097/igc.0b013e3182738361
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis for Therapeutic Targets and Prognostic Markers in Low-Grade Endometrial Stromal Sarcoma

Abstract: In patients with LGESS, c-kit and PDGFR were expressed in higher portions of patients, suggesting that imatinib mesylate should be investigated as a potential targeting agent. Both p53 and ki67 demonstrated strong prognostic implications, suggesting that further evaluation using these markers is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
(20 reference statements)
3
20
0
Order By: Relevance
“…Another popular proliferation biomarkers is Ki-67 which in one study was expressed in 2 of 11 LGESS and predicted recurrence [21]. In agreement with this, Ki-67 and P53 expression occurred in 54% and 10% of LGESS (total 39 cases) and this also was associated with worse survival [22]. Although the pre-2003 diagnostic criteria were used in the latter two studies, it might be that increased proliferation in rigorously WHO2003 defined ESS, Low Grade tumors plays a prognostic role.…”
Section: Introductionmentioning
confidence: 62%
“…Another popular proliferation biomarkers is Ki-67 which in one study was expressed in 2 of 11 LGESS and predicted recurrence [21]. In agreement with this, Ki-67 and P53 expression occurred in 54% and 10% of LGESS (total 39 cases) and this also was associated with worse survival [22]. Although the pre-2003 diagnostic criteria were used in the latter two studies, it might be that increased proliferation in rigorously WHO2003 defined ESS, Low Grade tumors plays a prognostic role.…”
Section: Introductionmentioning
confidence: 62%
“…19 The other study examined 39 low-grade endometrial stromal sarcomas and reported 82% (32 of 39) positivity in these tumors, 20 However, the positive tumors were also reported to show only very focal KIT immunostaining (o5% based on the representative KIT immunostaining image). 20 It is unclear what accounted for greater frequency of KIT positivity in this larger study as the primary antibody (Dako antibody for all) or the dilution used did not appear to be a contributing factor. Among the four studies evaluating KIT staining in high-grade endometrial stromal sarcomas/ undifferentiated endometrial sarcomas, a total of 7 out of 18 tumors (39%) showed focal (o30%) positivity.…”
Section: Discussionmentioning
confidence: 99%
“…The protein encoded by MKI67 gene is widely used as a marker of proliferation in routine pathological investigations and the nuclear protein Ki67 is an established prognostic marker in cancer (101)(102)(103)(104)(105). The prognostic value of Ki67 in mesothelioma is known since 1998 when it has been reported a statistically significant difference between the survival of patients having a low and high Ki67 index (P<0.001) (106); subsequently other studies confirmed its prognostic significance (70,71).…”
Section: Clinical Implications Of Overexpressed Genes In Mpmmentioning
confidence: 79%